Potential output, output gap and high inflation in Argentina (2007-2015) - Campos, Luciano (Estudios de Economía, 2020)
I investigate the causes of the high inflation Argentina experienced from 2007 to 2015. To do so, I estimate the potential output and the output gap using the Blanchard-Quah decomposition for this country and compare it to the estima- tions I obtained for other economies in the region were inflation was kept under control. I find that there are some country specific patterns in Argentina that can explain the high inflation observed during the analyzed years. First of all, Argentinean potential output grew at a slower pace than the rest of the countries, most notably since 2011. Second, there has been in Argentina a positive and increasing output gap since 2007, which was highly correlated with the inflation rate. Last, a comparison between the actual interest rate and the one derived from an ex-post monetary policy rule reveals that monetary policy was too lose in Argentina but that has not been the case in the rest of the countries. The policy implications of these findings are straightforward: Argentina could have reduced inflation by following a monetary rule, just like the rest of the Central Banks in the region seem to have done.